The colours of exploitation: smuggling of Rohingyas from Myanmar to Malaysia - Andika Ab. Wahab, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Irregular migration is inevitable due to a long history of systematic human rights persecutions facing the Rohingyas in Myanmar. Their irregular migration has been made possible by the presence of smuggling networks whose business operations were motivated by multiple factors beyond merely profit seeking. Essentially, smuggling of migrants is often associated with element of mutual benefit between the two parties namely the smuggler and migrant. Additionally, a migrant who has agreed to be smuggled has given his or her consent. Given the various factors that motivate such smuggling service, the question arises, does aspect of exploitation exist in this mutually beneficial transaction? If yes, on what basis does it constitute exploitation? In the event where smuggling service is offered to assist Rohingyas to ensure safe migration and to flee from long human rights persecutions, can this be considered as an act of exploitation? Are there any extreme acts where smugglers commit on physical violence, harassment and various forms of manipulation against the victims? This study seeks to explore on these research inquiries. Despite the existence of elements such as mutual benefit and consent throughout the smuggling of Rohingya victims, this study found that exploitation still exists. In the event where smuggling of Rohingyas were inspired by the spirit of brotherhood and solidarity, the study argues that the failure of smugglers to uphold their prima facie moral obligation not to extract benefit from Rohingyas who cannot reasonably refuse their offers – still account to exploitation. Worse, the use of deception, coercion, forced labour and forced marriage were not uncommon employed by the smugglers in order to intimidate and threaten victims. This suggests that some smuggling activities are likely to turn into trafficking in persons incidents where aspects of mutually beneficial and victims’ consent are no longer applied. Findings in this study were derived from a yearlong field work in 2013 by engaging Rohingya refugees, asylum seekers as well as Rohingya community leaders and activists in Peninsular Malaysia.